Pemberdayaan Pengelolaan Kelompok Nelayan di Desa Labetawi Kecamatan Dula Utara Kota Tual - M Faqih Seknun; Janaba Renngiwur (IAIN AMBON, 2022)
One of the enhancements in welfare economics of the community, especially Village Labetawi Village. All the time, the local community has their main job as a fishing community and untiltoday they have been managing fishery products conventionally the fishery products they produce. This condition has been occurred for a long time, more than 50 to 60 years until now. This community service aims to provide assistance to the local community in terms of providing knowledge about how to manage the marine catch and management as a living asset of the local village community in that village with the purpose to change the old traditional way to the modern way which is easier and more affordable in terms of changes in the local community based on the real conditions that occur in that village. The data collection techniques used by the researcher in the implementation of this service are in several ways, namely: Interview, observation and documentation. Based on the result based on the results of the implementation of community service activities in the Labetawi Village. success in getting several things, among others implementation of service activities, namely empowering housewives through making fish crackers and fish successfully implemented with large indications of the people enthusiasm, especially in socialization and demonstration activities accompanied by a follow-up from the women's group in making fish crackers and fish sauce. Second, Community service activities are one way out for the problems faced by the community, especially Labetawi village community in the field of fish processing and inspire the community to be more confident in business development in order to improve the welfare and economy of the local community. Lastly, this community service activity has been able to create cooperation between teams that carry out community service well and responsibly.